2020
DOI: 10.1111/1462-2920.15322
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic conditions outweigh microbial origin during bacterial assembly in soils

Abstract: Summary Understanding the processes guiding microbial community assembly in soils is essential for predicting microbiome structure and function following soil disturbance events like agricultural soil fumigation. However, assembly outcomes are complex and variable, being affected by both selective abiotic forces and by the history of colonizing microorganisms. To untangle the interactions between these factors, we conducted a controlled microcosm study tracking bacterial assembly in cleared soils over 7 weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…One possible reason for the variation in alpha diversity could be that the feces we used via the restoration method may have changed the Acetobacter abundance of the gut‐restoration treatment such as via competition of bacteria during the recolonization process. The high diversity in the gut‐restoration treatment we found was also observed in recolonized soil samples (Kaminsky et al, 2021 ); in that study, beta diversity also indicated that the microbiomes of these samples were similar to each other.…”
Section: Discussionsupporting
confidence: 82%
“…One possible reason for the variation in alpha diversity could be that the feces we used via the restoration method may have changed the Acetobacter abundance of the gut‐restoration treatment such as via competition of bacteria during the recolonization process. The high diversity in the gut‐restoration treatment we found was also observed in recolonized soil samples (Kaminsky et al, 2021 ); in that study, beta diversity also indicated that the microbiomes of these samples were similar to each other.…”
Section: Discussionsupporting
confidence: 82%
“…Our study used a dilution-to-extinction approach to recolonize thrice autoclaved soils, similar to a previous study by Wagg et al [ 67 ] albeit with only a single autoclave step. Autoclaving can break down soil nutrients and may impact other soil physicochemical properties [ 76 ] but allows for large-scale processing of soil for performing experiments at scale [ 28 , 33 , 74 , 77 , 78 ] and more closely resembles agricultural management practices such as soil steaming. We have previously observed greater unintended microbial regrowth in gamma irradiated soils relative to autoclaved soils (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, fungal composition in microbially-inoculated treatments were more dissimilar to the water control and had lower within-treatment similarity relative to bacterial composition, suggesting that stochasticity may play a greater relative role in fungal assembly [68]. It should be noted that both deterministic and stochastic processes influence microbial assembly and it can be dependent on spatial scale, temporal influences and environmental factors [68][69][70][71][72][73][74]. When comparing the two soils, we observed similar assembly patterns for bacterial composition, but opposing patterns for fungal composition.…”
Section: Discussionmentioning
confidence: 99%
“…This result implies that functional convergence towards the low DOC phenotype may be a more energetically favorable and likely outcome following multiple rounds of serial propagation, and highlights the likelihood of alternative stable states in community composition and functioning. An alternative outcome could have been that composition also converged in later generations; however, this would likely only be expected under extremely harsh conditions with strong selective community filtering ( 59 , 60 ). Our data show that community structure and interactions impacted both functional stability and the magnitude of DOC abundance, and that fragmentation of microbial interactions was associated with more stability in DOC abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Biological legacy effects have been shown to be major drivers of fungal composition at multi-year timescales during plant litter decomposition in a field experiment ( 58 ); however, the lack of temporal effects may also be a consequence of niche persistence, slow fungal growth rates during the short 28-day incubation, or failure of the liquid resuspension-inoculation method to effectively transfer some fungal taxa could lead to lower fungal richness and dispersion during later generations. In soils, abiotic effects on bacterial composition have been reported to be much larger than biotic origin signatures ( 60 ). In this experiment, the repetitive dilution approach used to inoculate the microcosms over multiple generations would have greatly reduced the carryover and influence of disparate abiotic factors from each natural soil inoculum, especially in later generations, leaving microbiome legacy to be a primary driver of community assembly.…”
Section: Discussionmentioning
confidence: 99%